Cultural degeneration and Newspapers - Farooq Adil (بازیافت)
The study aims to determine the correlation between the employment of language and the decay of the Normative framework and degeneration of societal norms. It has been seen that irresponsible statements for politicking are generally picked up and hyped by the media. Further, the degradation of language and personal allegations put politics away from partisan political domain resulting into desensitisation of the society. This correlation of lousy language and desensitisation of the society has not been studied theoretically in Pakistan. The assessment, in this study, has been carried out in light of the parameters set out by the Theory of Desensitisation under a larger framework of General Agression Theory delineating that abnormal shifts to neo-normal if repeated with regular intervals. The study confines to two watershed years i.e, 1958 when Pakistan faced first constitutional breakdown and 2013 onwards resulting into polarisation. In order to analyse, a widely read newspaper selected that have been in circulation virtually all over Pakistan since its creation. The editorials, statements of political leaders, reporting of incidents have been studied precisely that determined the course of the political history of Pakistan and the fissures in the social texture of the country. It has been observed that the more such content is given coverage, the more society and polity gets desensitised. Moreover, publication of such content is incremental in nature, that is to say, it expands in terms of coverage and intensity as time goes by. The study concludes that desensitization has been growing over the years resulting into degeneration of the societal norms.